KEMAMPUAN POLISAKARIDA MANNAN SEBAGAI ORAL ADJUVAN VAKSIN AVIAN INFLUENZA PADA AYAM BROILER - Syahruddin Syahruddin; Nahrowi Nahrowi; Yatno Yatno (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2020)
Polysaccharides contain mannan (PM) from palm kernel meal (PKM) potential as leader pathogen microorganism and enhancing the immune responses. The objective of the study was to evaluate efficacy of PM as oral adjuvant in increasing AI H5N1 antibody titer and immunoglobulin A (IgA) in serum of broiler thirty chickens age 1 - 6 weeks were divided onto five groups and assigned randomly to five vaccine treatments i.e : un-vaccinated birds (R0A), birds vaccinated with antigen H5N1 + 0 µg PM (R0B), birds vaccinated with antigen H5N1 + 50 µg PM (R1), birds vaccinated with antigen H5N1 + 100 µg PM (R2) and birds vaccinated with antigen H5N1 + 200 µg PM (R3). The results showed the treatment did not reduce broiler body weight (PM is not toxic). AI H5N1 antibody titer increased significantly (P0.05) one week after the first vaccination, serum IgA of broiler also increased significantly (P0.05) two weeks after the second vaccination. R3 treatment (200 μg PM) produce higher HI antibody titer ≤ 5 log2 and serum IgA 1.6 fold higher compared with those of broiler received R0A and R0B. It can be concluded that PM can increase the immune response in broiler chickens and can be used as an adjuvant for inactive AI vaccine.